Management of infections caused by extended-spectrum β–lactamase-producing Enterobacteriaceae: current evidence and future prospects. Issue 3 (4th March 2018) - Sheu, Chau-Chyun; Lin, Shang-Yi; Chang, Ya-Ting; Lee, Chun-Yuan; Chen, Yen-Hsu; Hsueh, Po-Ren
ABSTRACT: Introduction : The spread of extended-spectrum β–lactamase (ESBL)-producing Enterobacteriaceae has become a major public health threat worldwide. Area covered : A thorough systematic literature review describing the current evidence and future prospects of therapeutic options for infections caused by ESBL-producing Enterobacteriaceae . Expert commentary : The methods of detecting ESBLs have been evolving. The Clinical and Laboratory Standards Institute and the European Committee on Antimicrobial Susceptibility Testing lowered the MIC breakpoints of cephalosporins against ESBL-producing Enterobacteriaceae in 2010. Phenotypic testing for ESBLs is no longer recommended. Instead, the selection of appropriate antimicrobial agents largely depends on the report of minimum inhibitory concentrations (MICs). To date, therapeutic options for these multidrug-resistant organisms remain limited. The clinical efficacy of piperacillin/tazobactam and cefepime on in vitro -susceptible ESBL-producing Enterobacteriaceae remains a concern. Many studies found an in vitro-in vivo discordance based on current breakpoints. Carbapenems are the most reliable antibiotics for severe infections caused by ESBL-producing Enterobacteriaceae . However, their overuse has led to a serious problem of increasing drug resistance. Recently, ceftolozane/tazobactam and ceftazidime/avibactam have been approved for the treatment of complicated urinary tract infections and complicated intra-abdominal infections. The introduction of these new β-lactam/β-lactamase inhibitor combinations offers new carbapenem-sparing options for the treatment of ESBL infections.